Yield and quality responses of Egyptian white garlic (Allium sativum L.) and wild garlic (Tulbaghia violacea Harv.) to nitrogen nutrition - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2010.